(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2020)
miRNAs is a class of nano-sized non-coding RNAs that regulate the expression of genes, and associated with many physiological and pathological processes, especially cancer. The expression of many genes is regulated by the binding of their mRNA with miRNA, so it is required to identify which candidate genes of oncogenesis and to what extent can interact with miRNA. The purpose of this work was to establish the characteristics of the interaction of known 3707 miRNA with mRNA of 38 candidate esophageal adenocarcinoma genes. It has been identified, that 84 miRNAs have binding sites in 31 mRNAs of genes at 5’UTR, CDS, and 3’UTR and the average free binding energy (ΔG) of miRNAs with mRNAs was -121 kJ/mole, -118 kJ/mole and -113 kJ/mole, respectively. 19 associations of miRNAs and mRNA of genes with a free energy of interaction more than -120 kJ/mole are recommended for the diagnosis of esophageal adenocarcinoma. The mRNAs of most genes containing two or more miRNA binding sites with overlapping of their nucleotide sequences form clusters. Based on the obtained results, associations of miRNA and mRNA of candidate genes are recommended to develop methods for early diagnosis of esophageal adenocarcinoma. Key words: mRNA, miRNA, genes, oncological diseases, esophageal adenocarcinoma